Karakterisasi Fisikokimia dan Mikrobiologis Terasi dari Nusa Tenggara Barat - Naufali, Muhammad Nizhar; Pravitri, Kartika Gemma; Ulpiana, Mia; Hidayatulloh, Arbi (Pro Food, 2025)
Shrimp anchovy paste is a traditional fermented condiment widely consumed in Asia. Regional variation in raw material selection and processing practice may affect physicochemical composition and microbial ecology, with implications for quality and safety. This study characterized the physicochemical and microbiological properties of shrimp anchovy paste produced in Sumbawa, East Lombok, and Central Lombok. Samples were analysed for proximate composition, texture, colour, amino acid profile, total plate count, lactic acid bacteria enumeration, and cell morphology. Statistical differences were evaluated by one way analysis of variance and Duncan multiple range test using SPSS version 26. Moisture content increased from Sumbawa (37.83%) to East Lombok (43.25%) and Central Lombok (46.17%). Ash content was highest in Sumbawa (28.09%) and lowest in Central Lombok (18.27%). Protein was substantially lower in East Lombok (12.96%) compared with Sumbawa (23.23%) and Central Lombok (23.05%). Fat and instrumental hardness did not differ significantly among regions. Amino acid analysis identified glutamic acid as the dominant free amino acid, most abundant in Central Lombok (25685 ppm) and Sumbawa (23560 ppm). Microbiological profiling indicated the highest total plate count in Sumbawa (2.79 log CFU/mL) and the highest lactic acid bacteria count in East Lombok (2.57 log CFU/mL). Cell morphology revealed Gram negative bacilli in Sumbawa and Gram positive bacilli in East and Central Lombok. Regional differences in raw material ratio, salt application, drying regime, and microbial succession drive variation in composition and microbiology of shrimp anchovy paste.